If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2 = 12 + x Reorder the terms: 2 + 7x = 12 + x Solving 2 + 7x = 12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 7x + -1x = 12 + x + -1x Combine like terms: 7x + -1x = 6x 2 + 6x = 12 + x + -1x Combine like terms: x + -1x = 0 2 + 6x = 12 + 0 2 + 6x = 12 Add '-2' to each side of the equation. 2 + -2 + 6x = 12 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = 12 + -2 6x = 12 + -2 Combine like terms: 12 + -2 = 10 6x = 10 Divide each side by '6'. x = 1.666666667 Simplifying x = 1.666666667
| -16x-20=-13x+55 | | (a+b+c)*(a+b-c)= | | 7x^2+28x-315=0 | | 10=42-2x | | 7x+21=4+2x | | 6(7+2x)=114 | | 2x-3+5x-8=6x+54 | | x^2+4x+10=7 | | x^2+2x=1000 | | 5a-6=3a-8 | | 0=6x^2+5sp-6p^2 | | 8(e-1)=5e+2 | | 3x^2-54x+240=0 | | 6x^2+5sp-6p^2=0 | | 14x+1=21x+4 | | .25x+9=13 | | 3y^2-12y-8=0 | | 6x^2+1x-5=0 | | 1=6x+4 | | 5(x+2)=12+x | | 29x-13y=11 | | 4x+5x-y+3x= | | x^2+3x-2=-2 | | ln(2y-5)-lny+3=0 | | 5x-7=2x+4 | | ym=bd | | lny-5ln+3=0 | | (2x+18)(3x+5)(2x+17)=180 | | 12+3x=7x+12 | | 4a+3=31 | | 8-x=x-5 | | x/8+3=15 |